Interviewing to Detect Lies About Opinions: The Devil’s Advocate Approach - Vrij, Aldert; Leal, Sharon; Fisher, Ronald P. (Advances in Social Sciences Research Journal, 2023)
The verbal cues lie tellers spontaneously report during interviews are weak and unreliable (DePaulo et al., 20023; Vrij, Hartwig, & Granhag, 2019). Researchers therefore asked for interview protocols to be developed that would elicit such verbal cues (Vrij & Granhag, 2012). Ten years later several interview protocols have emerged (Vrij, Granhag et al., 2022), including Cognitive Credibility Assessment (Vrij, Fisher, & Blank, 2017; Vrij, Mann et al., 2021), Reality Interviewing (Bogaard et el., 2019; Colwell et al., 2007), the Strategic Use of Evidence (Granhag & Harwig, 2015; Hartwig et al., 2014) and the Verifiability Approach (Nahari, 2019; Palena et al., 2021). All these interview protocols focus on distinguishing between truthful and deceptive statements about alleged activities. However, practitioners are also interested in detecting lies when people discuss their opinions. The Devil’s Advocate Approach is the only interview protocol we are aware of aimed to distinguish between truthful and deceptive opinions. In this article we present the (scarce) Devil’s Advocate Approach research conducted to date.